Magnetic and Chemical Analyses Of Ores and Mill Products Containing Magnetite and Ilmenite - Erkki Laurila (The American Institute of Mining, Metallurgical, and Petroleum Engineers, 1951)
INVESTIGATION of the methods of analyses for magnetite and ilmenite in the Otanmäki iron-titanium ore and respective mill products has resulted in certain improvements in the methods conventionally employed. The outcome of the investigations is summarized as follows: 1-Development of a diamond-drill core analyser for the determination of magnetic susceptibility of drill cores containing magnetic minerals. 2-Development of a magnetite-ilmenite analyser for pulverized products. 3-Development of a potentiometric method of chemical analysis for the determination of iron, vanadium, and titanium in succeeding steps from one test sample. 4-Proposal for a continuous and automatic magnetite assay method.